Economic Analysis of A Coal Mining Project Under the Industrial Uncertainty Using Real Options Valuation - Indramantanu, Satwika; Arif Sumirat, Erman (The Indonesian Journal of Business Administration, 2018)
Abstract. A well-crafted company assessment is a tough task that requires detailed analysis, assumption that can be justified and applied with a clear synthesized. Conventional DCF analysis, which is temporarily used by most investment communities, has its weaknesses. This model has limitations in the ability to combine future flexibility. The company's assessment is a subjective process that needs to combine future expectations amid the industry's uncertainties. The DCF model is presented on condition that investment decisions are naturally defined by assuming that management takes a passive role. However, this is contrary to the management philosophy and expectations of the investment community. Real option valuation (ROV) allows for flexibility. In the DCF model, the ROV recognizes that uncertainty is not only represented by downside risks. The ability of firms to adjust future investment decisions when facing a dynamic environment also leads to a decrease in potential risk and ability to capture potential increases. Keywords:  capital budgeting, coal mining, discounted cash flow, real options, valuation